An Analysis of Culture Shock from West to East as Seen in Reilly’s The Tournament - Desma Lina; Dwi Budi Setiawan (Universitas Teknokrat Indonesia, 2017)
This article will explore about west and east cultures in the sixteenth century and some issues which occurred when both cultures encounters. The issue that appears when both cultures encounter is that of culture shock. The purpose of this research is to disclose how culture shock happens when both culture, west and east meet. In this research, the writers use concept of culture as the foundation of the research. Further, the analysis is done by implementing Oberg’s culture shock theory. To arrange this research, the writers apply library study and descriptive-qualitative method. The data that collected by the writers are in the form of narration and quotation. The source of the data coming from a novel entitled The Tournament by Mathew Reilly. The result of the analysis shows that there are two types of culture that are found inside the novel, visible and invisible cultures. Visible culture consists of cultural artifacts that can be noticed easily. Meanwhile the invisible part of culture is a culture that cannot be noticed easily but it does exist and holds important role in human life. Further, the phenomenon of culture shock proven by the character of Elizabeth who experience all stages of culture shock which are Honeymoon stage (Excitement), Crisis stage (Depression), Development stage (Learning process) and Adjustment stage (Accepting).